Regional Innovation Patterns and the EU Regional Policy Reform: Toward Smart Innovation Policies - Camagni, Roberto; Capello, Roberta (Growth and change, 2013)
The present debate on regional policy design to fit the Europe 2020 Agenda calls for additional reflections on the way sectoral policies, like innovation policies, can be translated appropriately into a regional setting. The paper enters the debate on smart specialization strategies by stressing the need to overcome the simplistic dichotomy between core and periphery in the Union and between an advanced “research area” (the core) and a “co‐application area” of general purpose technologies to local technological specificities (the periphery). The geography of innovation is much more complex than a simple core‐periphery model, and the logical pathway toward innovation is much more complex than the linear model of research and development‐invention‐innovation direct link: the innovation patterns are differentiated among regions according to their regional context conditions. The identification of specific “innovation patterns” is necessary to design “smart innovation” policies. The paper presents a critique to the smart specialization debate, suggests a new taxonomy of European innovative regions based on their innovation patterns, and proposes innovation policies for each regional mode of innovation.